Implementasi Media Pembelajaran Dengan Enggunakan Epro Dan E-Book Dalam Meningkatkan Antusias Belajar Peserta Didik Di Desa Kepuhdoko - Waqfin, Mohammad Saat Ibnu; Galih , Ananta; Abdullah, Hanif; Jamaludin, Jamaludin; Nurlia, Zulaikhotun (Institut Teknologi dan Sains Mandala, 2022)
Since the implementation of the online learning system, not a few students find it very difficult to learn. In addition, the level of student enthusiasm for learning is decreasing and even disappearing. This is in accordance with the explanation of one of the guardians of students in Kepuhdoko Village. He explained that today's students prefer to hold gadgets rather than holding books. After the pandemic period has begun to recede, the government has a policy that schools can conduct offline learning but with a shortened learning period or can be called Limited Face-to-face Learning (PTMT). This applies as a result of the ongoing pandemic. This learning system also applies in Kepuhdoko village. In this case, our focus in this activity is students from the hamlets of Kepuh and Semaden at the SD/MI level. The education system in these two hamlets also follows the rules of the Ministry of Education and Culture, which is to apply limited face-to-face learning. However, it is undeniable that students need a process to restore feelings of pleasure or enthusiasm to learn directly with educators. Limited face-to-face learning (PTMT) is a transitional learning scheme, where students will take online and offline (face-to-face) courses before fully switching to a 100% offline learning scheme with several conditions and following health protocols. In the village of Kepuhdoko, there are 2 basic education institutions, namely MIS Darul Ulum Kepuhdoko and SDN Kepuhdoko. At MIS Darul Ulum Kepuhdoko teaching and learning activities use a collaborative system between the face-to-face learning system and the online learning system.